2007
DOI: 10.1021/bc070062f
|View full text |Cite
|
Sign up to set email alerts
|

5‘-Modified G-Quadruplex Forming Oligonucleotides Endowed with Anti-HIV Activity:  Synthesis and Biophysical Properties

Abstract: Oligodeoxyribonucleotides of sequence d(5'TGGGAG3') carrying bulky aromatic groups at the 5' end were found to exhibit potent anti-HIV activity [Hotoda, H., et al. (1998) J. Med. Chem. 41, 3655-3663 and references therein]. Structure-activity relationship investigations indicated that G-quadruplex formation, as well as the presence of large aromatic substituents at the 5'-end, were both essential for their antiviral activity. In this work, we synthesized some representative examples of the anti-HIV active Hoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
44
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 34 publications
14
44
0
Order By: Relevance
“…Structural-activity relationship analysis showed that the presence of a DNA duplex and hydrophobic groups was crucial for the anti-HIV-1 activity observed, although the locations of the hydrophobic groups in the duplex and the sequence composition seemed not to be critical to the activity of the respective DNA duplexes tested. The modified DNA duplexes showed anti-HIV-1 activity at low M concentrations comparable to those of a previously described G-quadruplex HIV-1 entry inhibitor (17)(18)(19)(20)(21)(22)(23)(24). These duplex inhibitors were found to be interacting with the HIV-1 gp41 NHR deep pocket to prevent 6HB formation between the gp41 NHR and CHR.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Structural-activity relationship analysis showed that the presence of a DNA duplex and hydrophobic groups was crucial for the anti-HIV-1 activity observed, although the locations of the hydrophobic groups in the duplex and the sequence composition seemed not to be critical to the activity of the respective DNA duplexes tested. The modified DNA duplexes showed anti-HIV-1 activity at low M concentrations comparable to those of a previously described G-quadruplex HIV-1 entry inhibitor (17)(18)(19)(20)(21)(22)(23)(24). These duplex inhibitors were found to be interacting with the HIV-1 gp41 NHR deep pocket to prevent 6HB formation between the gp41 NHR and CHR.…”
Section: Discussionsupporting
confidence: 67%
“…In contrast to Hotoda's quadruplex inhibitors d(TGGGAG) 4 (17)(18)(19)(20)(21)(22)(23)(24), the duplex inhibitors reported in this paper can be extensively modified based on the location of the hydrophobic groups and skeleton length, thereby presenting more opportunities for modification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…T1 contained three hydrophobic groups (one TBDPS and two DMTs) at each end of the helix. The IC 50 for T1 was 1.8 -0.7 mM, comparable to the previously reported IC 50 values of duplex and quadruplex inhibitors [3][4][5][6][7][8][9][10][11][12][13][14][15]. T2 had no hydrophobic group modifications and did not show the anti-HIV-1 fusion activity.…”
Section: Odns and Triplexessupporting
confidence: 82%
“…Nearly 20 years ago, researchers discovered a category of DNA G-quadruplexbased inhibitors that display an anti-HIV-1 fusion activity [2]. Among these inhibitors, the most representative structure is Hotoda's sequence, d(TGGGAG), which interacts with the V3 loop or CD4-binding site of viral glycoprotein 120 (gp120) [3][4][5][6][7][8][9][10][11][12][13]. Recently, we designed a novel class of DNA duplex-based HIV-1 fusion inhibitors, which have hydrophobic groups at several selected positions [14,15].…”
Section: Introductionmentioning
confidence: 99%